Performance of women-managed plots compared to men-managed plots among smallholder maize farmers in western and central Ethiopia - Paswel Phiri Marenya; Gebrelibanos Gebremariam; Dil Bahadur Rahut (Journal of Applied Economics, 2021)
A more targeted approach towards improving women's access to agricultural innovations is key to increase the overall agricultural productivity. This paper uses gender-disaggregated household and plot-level survey data from Ethiopia to explore the impacts of multiple agronomic practices disaggregated by the sex of the plot manager. Using a multinomial endogenous switching regression methodology, after controlling for endogeneity arising from observed and unobserved heterogeneity, we found that multiple agronomic practices have a positive and significant effect on maize yields and maize income. Crucially, subject to demographics, plot quality and agronomic practices (among others), we found that women-managed plots (WMP) had treatment effects (yields) that were statistically the same as those of men-managed plots (MMP) (and nominally higher in a number of cases).
Keywords: 330; endogenous switching regression; Ethiopia; gender; heterogeneity; Technology adoption; welfare